A computational approach for modelling composite slabs in fire within OpenSees framework. (15th March 2022) - Qiu, Jin; Jiang, Liming; Anwar Orabi, Mhd; Usmani, Asif; Li, Guoqiang
Highlights: A unified reference plane with offset of shell sections enables convenient modelling of composite slabs. Defining the ribbed section and tapered profile steel are integrated into the section. Built-in allocation of layer temperatures is enabled to consider the realistic distribution. This approach has been verified and validated with an extensive collection of cases without particular calibration. Abstract: Modelling tall buildings responding to fires, especially multi-floor fires, requires the consideration of composite slabs as the composite action can significantly affect the structure fire response. Modelling composite slabs in fire is tedious and complex due to the existence of ribs and complicated thermal action. In view of the complexity of the existing modelling approaches, this paper aims to propose a computational approach for modelling composite slabs in fire in the open-source program of 'OpenSees for fire'. The proposed approach adopts a unified reference plane in the shell element discretization along with built-in approximation of the ribbed section and temperature loading. The modelling approach is incorporated into a new version of layered shell thermal section with a vision of enabling efficient modelling of tall buildings in fire. Benchmark tests are performed using T-shaped plain concrete beams to verify the approach. A collection of tests on composite slabs or composite floor systems are then modelled to extensively validate the approach with respect to the ambient loading and fire tests. Validation results demonstrate good performance of the modelling approach even without extra calibration. The work implemented in OpenSees will be made open source and can significantly simplify the modelling efforts of including multiple floors of composite slabs in a tall building model when investigating its fire performance.